The Neutrophil-to-Albumin Ratio (NAR): A Novel Index in Relation to Clinical Symptoms, Quality of Life, and Psychological Status in Diarrhea-Predominant Irritable Bowel Syndrome (IBS-D) - Huang X; Li A; Long P; Liu Y; Zhou Z; Pan Y (Dove Medical Press, 2024)
Xijing Huang,1,2,* An Li,1,2,* Ping Long,1,2,* Ya Liu,1 Zhou Zhou,1 Yan Pan1 1Department of Gastroenterology, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 2Clinical Immunology Translational Medicine Key Laboratory of Sichuan Province, Sichuan Provincial People's Hospital, University of Electronic Science and Technology of China, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Yan Pan, Email panyan2211@163.comIntroduction: Irritable bowel syndrome (IBS) is a common gastrointestinal disorder characterized by chronic abdominal pain and alterations in bowel habits. Despite the importance of biomarkers in disease management, the quest for precise and non-invasive biomarkers for IBS continues.Methods: This study focuses on investigating the clinical significance of the neutrophil-to-albumin ratio (NAR) as a potential biomarker in IBS. A cohort of 86 patients diagnosed with diarrhea-predominant IBS (IBS-D) and 106 healthy individuals were assessed for clinical symptoms, quality of life (QOL), psychological status, as well as serum and mucosal cytokine production.Results: Our findings revealed that NAR levels were notably elevated in patients with IBS-D compared to healthy controls. Positive correlations were observed between NAR levels and IBS clinical symptoms, while negative correlations were noted with QOL. Additionally, NAR showed positive associations with anxiety and depression scores, along with significant relationships with cytokine production (serum IL-6, TNF-α, IL-1β, IL-17A, GM-CSF, IFN-γ, MCP-1; mucosal IL-6, TNF-α, IL-1β, IL-17A) in IBS-D. Interestingly, patients with lower baseline NAR levels demonstrated potentially better clinical outcomes.Conclusion: The study underscores the potential utility of NAR as a novel biomarker in IBS, emphasizing its role in enhancing disease monitoring, understanding disease pathophysiology, and tailoring treatment strategies for patients with IBS-D.Keywords: irritable bowel syndrome, the neutrophil-to-albumin ratio, biomarkers, inflammation